2012
DOI: 10.1021/cm301387d
|View full text |Cite
|
Sign up to set email alerts
|

Complex Ammine Titanium(III) Borohydrides as Advanced Solid Hydrogen-Storage Materials with Favorable Dehydrogenation Properties

Abstract: Ammine metal borohydrides (AMBs), with high hydrogen contents and favorable dehydrogenation properties, are receiving intensive research efforts for their potential as hydrogen storage materials. In this work, we report the successful synthesis of three ammine titanium borohydrides (denoted as ATBs), Ti(BH 4 ) 3 •5NH 3 , Li 2 Ti-(BH 4 ) 5 •5NH 3 , and Ti(BH 4 ) 3 •3NH 3 via metathesis reaction of metal chloride ammoniates (TiCl 3 •5NH 3 and TiCl 3 •3NH 3 ) and lithium borohydride. These ATBs present favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 51 publications
8
55
0
Order By: Relevance
“…Future research may also address this issue, for example, by detailed analysis of the reaction mechanism for hydrogen absorption of dehydrogenated nanoconfined Al(BH 4 ) 3 ·6NH 3 treated with hydrazine in liquid ammonia similar to other B-N based materials. [24,[57][58][59][60][61] …”
Section: Trends For Ammine Metal Borohydridesmentioning
confidence: 99%
“…Future research may also address this issue, for example, by detailed analysis of the reaction mechanism for hydrogen absorption of dehydrogenated nanoconfined Al(BH 4 ) 3 ·6NH 3 treated with hydrazine in liquid ammonia similar to other B-N based materials. [24,[57][58][59][60][61] …”
Section: Trends For Ammine Metal Borohydridesmentioning
confidence: 99%
“…U.S. Department of Energy (DOE) set a target for practical H storage materials to have a gravimetric capacity of 5.5 wt% by 20174. The challenge is to dramatically increase storage capacity and reversibility at ambient conditions5. Carbon-based nanostructures and porous materials including fullerene, nanotube, and carbyne networks, have been proposed as potential H 2 storage media, thanks to their high surface-to-weight ratios, good reversibility and fast kinetics678910.…”
mentioning
confidence: 99%
“…These results led the authors to speculate that the chemisorption of H2 in these compounds might be reversible at temperatures lower than those of other types of hydrides, rendering such hydrides a potentially new class of intermediate -temperature hydrides. Furthermore, investigations on Ti(BH4)3·3NH3, Ti(BH4)3·5NH3, and Li2Ti(BH4)5·5NH3 by Yuan et al (2012) 219 revealed that high H2 adsorption capacities below T = 300 °C are possible. Especially noteworthy is the continuous release of H2 by Li2Ti(BH4)5·5NH3 and Ti(BH4)3·3NH3 at a constant temperature of T = 100 °C, with H2 adsorption capacities of ~ 9 wt%, which fulfills the requirements for vehicular applications.…”
Section: Hydrogen Storagementioning
confidence: 99%